2001
DOI: 10.1074/jbc.m010859200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mitogen-activated Protein Kinase Kinase Induces Apoptosis of Human Chondrocytes

Abstract: We previously have reported that the mitogen-activated protein kinase (MAPK) pathway is stimulated by adhesion of human chondrocytes to anti-␤ 1 -integrin antibodies or collagen type II in vitro. These mechanisms most likely prevent chondrocyte dedifferentiation to fibroblast-like cells and chondrocyte death. To investigate whether this pathway plays an essential role for the differentiation, phenotype, and survival of chondrocytes, we blocked mitogen-activated protein kinase/extracellular signal-regulated kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 44 publications
(46 reference statements)
8
114
1
2
Order By: Relevance
“…In other cell types, IGF-I survival signalling involves the activation of the PI3K/Akt pathway, although additional pathways appear to be capable of promoting survival [33,34]. In chondrocytes plated on to collagen, IGF-I stimulation of the ERK/MAPK signalling pathway was shown to prevent apoptosis [35]. Under the conditions used in the present study, significant cell death was not observed with inhibition of either the PI3K pathway or the ERK/ MAPK signalling pathway.…”
Section: Discussionmentioning
confidence: 49%
“…In other cell types, IGF-I survival signalling involves the activation of the PI3K/Akt pathway, although additional pathways appear to be capable of promoting survival [33,34]. In chondrocytes plated on to collagen, IGF-I stimulation of the ERK/MAPK signalling pathway was shown to prevent apoptosis [35]. Under the conditions used in the present study, significant cell death was not observed with inhibition of either the PI3K pathway or the ERK/ MAPK signalling pathway.…”
Section: Discussionmentioning
confidence: 49%
“…Western blot analysis was performed as described previously in detail [21]. Briefly, tenocyte proteins were extracted with lysis buffer [50 mM Tris/HCl (pH 7.2)], 150 mM NaCl, 1% (v/v) Triton X-100, 1 mM sodium orthovanadate, 50 mM sodium pyrophosphate, 100 mM sodium fluoride, 0.01% (v/v) aprotinin, 4 g/mL pepstatin A, 10 g/mL leupeptin and 1 mM PMSF for 30 min on ice.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…They activate different signal transduction pathways, such as the mitogen-activated protein (MAP) kinase pathway, and thus control proliferation, differentiation and survival of tenocytes [18,19]. Undisturbed cell-matrix interactions are essential for cell viability, and inhibition of the MAP kinase pathway can induce programmed cell death [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the role of p38 MAPK, ERK1/2 and JNK on MMP-1 and MMP-3 induction by B. burgdorferi, we examined expression of MMP-1 and MMP-3 in the presence of specific inhibitors for each pathway. Concentrations of inhibitors were selected based on prior studies of these inhibitors with chondrocytes (9,15,16,21,25,28,29,31,33,34). Cells were in- (Fig.…”
Section: B Burgdorferimentioning
confidence: 99%